Evidence for Faster X Chromosome Evolution in Spiders. (26th March 2019) - Bechsgaard, Jesper; Schou, Mads Fristrup; Vanthournout, Bram; Hendrickx, Frederik; Knudsen, Bjarne; Settepani, Virginia; Schierup, Mikkel Heide; Bilde, Trine
Abstract: In species with chromosomal sex determination, X chromosomes are predicted to evolve faster than autosomes because of positive selection on recessive alleles or weak purifying selection. We investigated X chromosome evolution in Stegodyphus spiders that differ in mating system, sex ratio, and population dynamics. We assigned scaffolds to X chromosomes and autosomes using a novel method based on flow cytometry of sperm cells and reduced representation sequencing. We estimated coding substitution patterns (d N /d S ) in a subsocial outcrossing species ( S. africanus ) and its social inbreeding and female-biased sister species ( S. mimosarum ), and found evidence for faster-X evolution in both species. X chromosome-to-autosome diversity (piX/piA) ratios were estimated in multiple populations. The average piX/piA estimates of S. africanus (0.57 [95% CI: 0.55–0.60]) was lower than the neutral expectation of 0.75, consistent with more hitchhiking events on X-linked loci and/or a lower X chromosome mutation rate, and we provide evidence in support of both. The social species S. mimosarum has a significantly higher piX/piA ratio (0.72 [95% CI: 0.65–0.79]) in agreement with its female-biased sex ratio. Stegodyphus mimosarum also have different piX/piA estimates among populations, which we interpret as evidence for recurrent founder events. Simulations show that recurrent founder events are expected to decrease the piX/piA estimates in S. mimosarum, thus underestimating the true effect of female-biased sex ratios. Finally, we found lower synonymous divergence on X chromosomes in both species, and the male-to-female substitution ratio to be higher than 1, indicating a higher mutation rate in males.